Adaptive behaviors in education institutions before and after COVID-19: A systematic literature review - Walugembe, Ahmad; Ntayi, Joseph; Olupot, Charles; Elasu, Joseph (Frontiers in Psychology, 2022)
Background The final third of the year 2019 was marked by the outbreak of the deadly coronavirus (COVID-19) pandemic. This virus paralyzed almost all the sectors of the economies including governments forcing education institutions to close. School closures resulted in significant learning losses and increased inequality in the education sector across the world. Despite these disruptions, however, available evidence reveals that some countries quickly developed adaptive mechanisms of emergency remote learning systems and other alternative methods such as televisions, telephone, Zoom, social media, Google classrooms, email, and even the post office to recover from learning losses. There are various studies conducted to assess the impact of this pandemic in different sectors and perspectives. However, systematic literature reviews documenting the adaptive behaviors in Education Institutions before and after COVID-19 are either sparse or non-existent. This systematic literature review study focuses on documenting the adaptation strategies and subsequent positive outcomes emerging from COVID-19 pandemic. The purpose of this study was to review published articles on adaptive behavior in education institutions. In particular, review the outcomes of the adaptive behavior and coping strategies/mechanisms over time. The study followed a systematic literature review approach as a core methodology for defining answerable research questions, searching literature for the best available evidence, appraising the quality of the evidence, collecting and aggregating available data for answering the identified questions. Material collection was carried out through Science Direct and Emerald data bases that are highly regarded as comprehensive and authoritative data bases. Other documents, especially the reports were collected from Google scholar search engine. search strings used include “COVID 19 adaptive behavior in education institutions” “COVID 19 coping strategies in education institutions”; “COVID 19 adaptation mechanisms in education sector; “COVID 19 Positive outcomes”; “Adaptive work behavior in education institutions” and “Adaptation strategies in education institutions” Findings and conclusions: Education institutions transitioned to remote teaching and learning strategies. Several studies report a number of positive outcomes ranging from personal, institutional and technology-based outcomes. Key among the technology based positive outcomes frequently reported in literature include increased innovations and increased digital resilience in education institutions among others.